PERSEPSI SISWA MENGGUNAAN APLIKASI "LEARN & SPEAK ENGLISH PRAKTIKA" SEBAGAI MEDIA DALAM MENINGKATKAN KEMAMPUAN BERBICARA: PERSEPSI SISWA MENGGUNAAN APLIKASI "LEARN & SPEAK ENGLISH PRAKTIKA" SEBAGAI MEDIA DALAM MENINGKATKAN KEMAMPUAN BERBICARA - Sitorus, Najwa Al Zuhda; Rahman Hz, , Benni Ichsanda (ELTIN Journal, 2025)
This study aims to analyze students' perceptions towards the use of the Learn & Speak English Praktika application in improving English speaking skills. The main focus of this study is how this application helps students improve their pronunciation, motivation, confidence, and vocabulary. This study uses a qualitative method with data collection through questionnaires and interviews with grade XI students in Medan. The results showed that the majority of students gave a positive response to this application. They felt that the real-time feedback feature helped improve pronunciation, AI-based interactions increased confidence, and the variety of conversation topics encouraged motivation and enriched their vocabulary. The implications of this study indicate that AI-based technology can be an effective alternative in language learning, especially in improving speaking skills. This application can be utilized by educators as an additional learning media that increases student engagement and independence in learning English. However, this study has several limitations, such as the limited duration of the study and the sample coverage which only included one school. Therefore, further research is recommended to examine the long-term impact of this application and compare it with conventional learning methods in a broader context.